Strontium ion adsorbent and preparation method thereof

By loading the hydroxyapatite crystals into the spherical bead-shaped resin, a spherical bead-shaped strontium ion adsorbent is formed, which solves the problems of easy loss and pressure drop of existing inorganic adsorbents when removing radioactive strontium-90 ions in nuclear power plants, and achieves an efficient and highly selective strontium ion removal effect.

CN119701888APending Publication Date: 2025-03-28KAIRUI ENVIRONMENTAL PROTECTION TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411816388.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing inorganic adsorbents have disadvantages such as easy loss and large pressure drop in applications, and it is difficult to efficiently and at low cost to remove radioactive strontium-90 ions generated in nuclear power plants.

Method used

By loading hydroxyapatite crystals on the spherical bead-shaped resin, a spherical bead-shaped strontium ion adsorbent is formed, and calcium ions and hydroxyapatite are loaded using ion exchange technology to improve adsorption performance.

Benefits of technology

It achieves efficient removal rate and selectivity of strontium ions, and can maintain efficient adsorption performance in the presence of a large number of coexisting cations, solving the problems of easy loss and pressure drop of existing adsorbents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701888A_ABST
    Figure CN119701888A_ABST
Patent Text Reader

Abstract

The invention discloses a strontium ion adsorbent and a preparation method thereof.The preparation method comprises the steps that cation exchange resin reacts with calcium hydroxide suspension / water-soluble calcium salt aqueous solution, so that calcium ions are loaded on the cation exchange resin in an ion exchange mode, and the cation exchange resin loaded with the calcium ions is obtained for use; and suspending the obtained cation exchange resin loaded with calcium ions in deionized water, then adding a mixed solution of phosphate and alkali into the system, forming hydroxyapatite precipitate in the resin and loading hydroxyapatite crystals in the cation exchange resin to obtain the spherical beaded strontium ion adsorbent. The hydroxyapatite-loaded resin provided by the invention has high-selectivity adsorption on strontium ions in a solution, and can remove the strontium ions with high selectivity in the presence of a large number of coexisting cations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adsorbent, in particular to a strontium ion adsorbent and a preparation method thereof, belonging to the technical field of functional adsorption materials. Background Art

[0002] The extensive use of fossil fuels over the past century has caused a large amount of carbon dioxide to be emitted into the atmosphere. As a greenhouse gas, the continuous increase in the concentration of carbon dioxide in the atmosphere has led to a continuous rise in global temperatures and triggered more and more catastrophic climate events. Increasing the proportion of non-fossil energy in energy supply is an effective means to achieve carbon neutrality and carbon peak. Nuclear energy, as a low-carbon and efficient non-fossil energy, plays an important role in alleviating the global energy crisis and reducing carbon dioxide emissions. However, with the development of the nuclear industry, a certain amount of radioactive waste is inevitably generated in scientific research and production activities. In addition, nuclear power accidents caused by uncontrollable external or internal conditions in nuclear power facilities have led to a large amount of radioactive wastewater. If radioactive wastewater is directly discharged into natural water bodies, radioactive elements will directly or indirectly harm people's health through the food chain. At present, the nuclear fuel of nuclear power plants is mainly uranium-235. The fission products of uranium-235 include a variety of radioactive elements, among which the half-life of further fission of the radioactive element strontium-90 is 28.5 years, which is one of the most serious radioactive wastes that endanger human health in the first hundred years of uranium-235 fission products discharged into the environment. Therefore, it is of great significance to remove this radioactive element efficiently and at low cost.

[0003] Methods for removing radioactive elements from nuclear wastewater include solvent extraction, chemical precipitation, ion exchange and adsorption, among which inorganic adsorbent adsorption is the most popular. Studies have found that some inorganic matrix adsorbents (ion exchangers) have good adsorption properties for strontium ions, such as bentonite, montmorillonite, sericite, clay, tungstate, hydroxyapatite, etc. There have been many studies on the adsorption of strontium ions by hydroxyapatite. Since the radius of strontium ions (0.112nm) is very close to the radius of calcium ions (0.099nm), strontium ions are easily exchanged with calcium ions in hydroxyapatite to adsorb strontium ions.

[0004] Inorganic adsorbents have the advantages of high thermal stability and high radiation stability. However, since most inorganic adsorbents such as hydroxyapatite are irregularly shaped fine particles, they have the disadvantages of easy loss and large pressure drop when used as column adsorption fillers, and their practical application is limited. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a spherical bead adsorbent for adsorbing strontium ions and a preparation method thereof in view of the deficiencies of radioactive ion adsorbents in the prior art. The present invention loads an inorganic adsorbent inside a spherical bead-shaped resin, specifically, loads hydroxyapatite crystals inside a spherical bead-shaped resin, the spherical bead-shaped resin serves as a carrier, and the hydroxyapatite crystals serve as a functional material for adsorbing strontium ions. The adsorbent and preparation method of the present invention have the advantages of high strontium ion removal rate and strong selectivity.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention first provides a method for preparing a strontium ion adsorbent, wherein calcium ions are loaded onto a cation exchange resin by ion exchange, and then hydroxyapatite crystals are loaded into the resin, comprising the following steps:

[0008] (1) Loading calcium ions:

[0009] The cation exchange resin is reacted with the calcium hydroxide suspension / water-soluble calcium salt aqueous solution, so that the calcium ions are loaded on the cation exchange resin by ion exchange, and the cation exchange resin loaded with calcium ions is obtained for standby use;

[0010] (2) Loading hydroxyapatite crystals:

[0011] The calcium ion-loaded cation exchange resin obtained in step (1) is suspended in deionized water, and then a mixed solution of phosphate and alkali is added to the system to form hydroxyapatite precipitation inside the resin and load the hydroxyapatite crystals inside the cation exchange resin to obtain a spherical bead-like strontium ion adsorbent.

[0012] In the above technical solution, in step (1), the cation exchange resin is a strongly acidic cation exchange resin or a weakly acidic cation exchange resin; preferably a weakly acidic hydrogen-type cation exchange resin or a strongly acidic sodium-type cation exchange resin; more preferably a weakly acidic hydrogen-type cation exchange resin.

[0013] In the above technical scheme, when the cation exchange resin is a weakly acidic hydrogen-type cation exchange resin, the specific method for loading calcium ions is: suspending calcium hydroxide in deionized water to form a calcium hydroxide suspension, adding the weakly acidic hydrogen-type cation exchange resin, and stirring at room temperature for 0.1 to 24 hours to allow the calcium ions to be loaded on the weakly acidic hydrogen-type cation exchange resin through ion exchange.

[0014] In the above technical solution, the mass ratio of calcium hydroxide to water in the calcium hydroxide suspension is 0.1-100:0.1-1000, and the ratio of the molar number of cation exchange groups on the weakly acidic hydrogen type cation exchange resin to the molar number of calcium ions is 2:1 to 2:1.5.

[0015] In the above technical scheme, when the cation exchange resin is a strongly acidic sodium type cation exchange resin, the specific method for loading calcium ions is: the strongly acidic sodium type cation exchange resin is loaded into a glass column, a water-soluble calcium salt aqueous solution is passed through the glass column at a flow rate of 0.1-1000mL / h, and then the resin is washed with deionized water at a flow rate of 0.1-1000mL / h for 0.1-24h, so that the calcium ions are loaded on the cation exchange resin through ion exchange.

[0016] In the above technical scheme, the water-soluble calcium salt aqueous solution is preferably a calcium chloride or calcium nitrate aqueous solution, the molar concentration of the solute in the water-soluble calcium salt aqueous solution is 0.001-10 mol / L, and the ratio of the molar number of cation exchange groups on the strongly acidic sodium type cation exchange resin to the molar number of calcium ions is 2:1 to 2:1.5.

[0017] In the above technical scheme, in step (2), the phosphate can be any water-soluble phosphate, preferably sodium phosphate; the alkali can be any strong or weak alkali, preferably sodium hydroxide or ammonia water with a mass concentration of 0.1-28%; in the mixed solution of the phosphate and the alkali, the mass concentration of the phosphate is 0.1-77%, and the mass concentration of the alkali is 0.1-50%; the ratio of the molar number of calcium ions loaded on the cation exchange resin loaded with calcium ions to the molar number of phosphate and alkali in the mixed solution of the phosphate and the alkali is (0.1-10):(0.1-10):(0.1-10), preferably 1:0.6:0.2.

[0018] In the above technical scheme, a mixed solution of phosphate and alkali is added to the system and the mixture is stirred at room temperature for 0.1-24 hours. After the reaction is completed, a sodium hydroxide solution is added dropwise under stirring conditions to make the mass concentration of sodium hydroxide in the system 4-6%. The temperature of the system is increased from room temperature to 80-100° C. (preferably 100° C.) and kept warm for 0.1-24 hours (preferably 2 hours).

[0019] In the above technical solution, the formation of calcium carbonate is avoided and the system is protected by inert gas during all operations.

[0020] The invention also provides a strontium ion adsorbent prepared by the preparation method, wherein the ion adsorbent is a spherical bead adsorbent.

[0021] The invention also provides a use of the strontium ion adsorbent for adsorbing strontium ions.

[0022] Compared with the existing technology, it has the following characteristics:

[0023] The resin loaded with hydroxyapatite has the advantages of high selective adsorption of strontium ions in the solution, and high removal rate and strong selectivity of strontium ions in the presence of a large number of coexisting cations. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the XRD spectrum of the KRSr-01 sample obtained in Example 1;

[0025] Figure 2 is the XRD spectrum of the KRSr-02 sample obtained in Example 2;

[0026] Figure 3 This is the XRD spectrum of the KRSr-03 sample obtained in Example 3. DETAILED DESCRIPTION

[0027] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1:

[0029] A strontium ion adsorbent is prepared by the following preparation method, which comprises the following steps:

[0030] (1) Loading calcium ions:

[0031] 4.55 g of calcium hydroxide (61.4 mmol, Mw74.09) was suspended in 500 mL of deionized water to form a calcium hydroxide suspension, and 20 g of a macroporous weakly acidic cation exchange resin of model D113 (wet, hydrogen type, water content 50.2%, exchange capacity 11.2 mmol / g, ratio of the molar number of cation exchange groups on the resin to the molar number of calcium ions 1:1.1) was added, and stirred at room temperature for 24 hours. Filter, wash the resin with deionized water for several times, filter, and vacuum dry the obtained resin to obtain 12.2 g of calcium ion-loaded resin. The above operation was completed under nitrogen protection.

[0032] Determination of calcium ion loading: Accurately weigh about 0.1g of calcium ion-loaded resin and place it in a 100mL conical flask, add 10mL of 2% nitric acid, cover with a stopper, shake at room temperature for 6 hours, transfer all the resin and nitric acid to a 100mL volumetric flask, rinse the conical flask three times with deionized water and transfer it to a volumetric flask, dilute to the scale, and use ICP to determine the calcium ion concentration of the solution in the volumetric flask. After measurement and calculation, the calcium ion loading of the calcium ion-loaded resin is 4.65mmol / g.

[0033] (2) Loading hydroxyapatite crystals:

[0034] Add 10g of the above-mentioned ion-loaded resin and 60mL of deionized water to a 250mL three-necked flask and stir. Separately, dissolve 4.57g of trisodium phosphate and 0.372g of sodium hydroxide in 40mL of deionized water to form a mixed solution of phosphate and alkali, and add this solution dropwise to the above-mentioned three-necked flask (the ratio of the molar number of calcium ions loaded on the resin to the molar number of phosphate and alkali in the added mixed solution of phosphate and alkali is 1:0.6:0.2). Continue stirring for 12 hours after the addition is complete. After the reaction is completed, add 30mL of 20% sodium hydroxide solution to the three-necked flask under stirring. After the addition is complete, heat to 100°C and keep warm for 2 hours. Cool and filter, and wash the resin with deionized water until the washing solution is neutral. Filter, vacuum dry the resin, and obtain 14.5g of hydroxyapatite-loaded resin, resin number: KRSr-01. The above operation was completed under nitrogen protection. Through X-ray diffraction (XRD) experiment ( Figure 1 ) proves the presence of hydroxyapatite in the resin. The XRD pattern of KRSr-01 sample is as follows Figure 1 shown.

[0035] Determine the loading amount of calcium ions and phosphorus ions: accurately weigh about 0.1g of the resin loaded with hydroxyapatite and place it in a 100mL conical flask, add 10mL of 2% nitric acid, cover the stopper, shake at room temperature for 6 hours, transfer all the resin and nitric acid to a 100mL volumetric flask, rinse the conical flask three times with deionized water and transfer it to the volumetric flask, dilute to the scale, and use ICP to determine the concentration of calcium and phosphorus in the solution in the volumetric flask. After measurement and calculation, the calcium and phosphorus loading amounts of the calcium ion loaded resin are 3.15 and 1.79mmol / g, respectively. The calcium ion loading amount is reduced relative to step (1) because the calcium ions are partially exchanged by ions in step (2).

[0036] Embodiment 2:

[0037] A strontium ion adsorbent is prepared by the following preparation method, which comprises the following steps:

[0038] (1) Loading calcium ions:

[0039] First, prepare a strongly acidic sodium type cation exchange resin: add 20g of a macroporous weakly acidic cation exchange resin of model D113 (wet, water content 50.2%, exchange capacity 11.2mmol / g) to 100mL of a 5% sodium hydroxide solution, shake for 6 hours; filter, wash the resin with deionized water until the washing solution is neutral, and obtain a strongly acidic sodium type cation exchange resin. Fill the 20g of strongly acidic sodium type cation exchange resin obtained after washing into a glass column (the inner diameter of the column is 1.2cm). 110mL of a 1mol / L calcium chloride solution flows through the above glass column at a flow rate of 50mL / h (the ratio of the molar number of cation exchange groups on the resin to the molar number of calcium ions is 2:1.5), and then wash the resin with deionized water at a flow rate of 100mL / h for 4 hours. Take out the resin, filter, and vacuum dry to obtain 11.8g of calcium ion-loaded resin. The above operation is completed under nitrogen protection.

[0040] Determination of calcium ion loading: Accurately weigh about 0.1g of calcium ion loaded resin and place it in a 100mL conical flask, add 10mL of 2% nitric acid, cover the stopper, shake at room temperature for 6 hours, transfer all the resin and nitric acid to a 100mL volumetric flask, rinse the conical flask three times with deionized water and transfer it to the volumetric flask, dilute to the scale, and use ICP to determine the calcium ion concentration of the solution in the volumetric flask. After measurement and calculation, the calcium ion loading of the calcium ion loaded resin is 4.73mmol / g.

[0041] (2) Loading hydroxyapatite crystals:

[0042] Add 10g of the above-mentioned ion-loaded resin and 60mL of deionized water to a 250mL three-necked flask and stir. Separately, dissolve 4.65g of trisodium phosphate and 0.378g of sodium hydroxide in 40mL of deionized water to form a mixed solution of phosphate and alkali, and add this solution dropwise to the above-mentioned three-necked flask (the ratio of the molar number of calcium ions loaded on the resin to the molar number of phosphate and alkali in the added mixed solution of phosphate and alkali is 1:0.6:0.2). Continue stirring for 12 hours after the addition is complete. After the reaction is completed, add 30mL of 20% sodium hydroxide solution to the three-necked flask under stirring. After the addition is complete, heat to 100°C and keep warm for 2 hours. Cool and filter, and wash the resin with deionized water until the washing solution is neutral. Filter, vacuum dry the resin, and obtain 14.8g of hydroxyapatite-loaded resin. Resin number: KRSr-02. The above operation was completed under nitrogen protection. Through X-ray diffraction (XRD) experiment ( Figure 2 ) proves the presence of hydroxyapatite in the resin. The XRD pattern of KRSr-02 sample is as follows Figure 2 shown.

[0043] Determine the loading amount of calcium ions and phosphorus ions: accurately weigh about 0.1g of the resin loaded with hydroxyapatite and place it in a 100mL conical flask, add 10mL of 2% nitric acid, cover the stopper, shake at room temperature for 6 hours, transfer all the resin and nitric acid to a 100mL volumetric flask, rinse the conical flask three times with deionized water and transfer it to the volumetric flask, dilute to the scale, and use ICP to determine the concentration of calcium and phosphorus in the solution in the volumetric flask. After measurement and calculation, the calcium and phosphorus loading amounts of the calcium ion loaded resin are 3.21 and 2.01mmol / g, respectively. The calcium ion loading amount is reduced relative to step (1) because the calcium ions are partially exchanged by ions in step (2).

[0044] Embodiment 3:

[0045] A strontium ion adsorbent is prepared by the following preparation method, which comprises the following steps:

[0046] (1) Loading calcium ions:

[0047] 20g of gel-type strong acid cation exchange resin (wet, sodium type, water content 48.9%, exchange capacity 4.55mmol / g) of model 001×7 was filled in a glass column (the inner diameter of the column was 1.2cm), 70mL of 1mol / L calcium chloride solution was passed through the above glass column at a flow rate of 50mL / h (the ratio of the molar number of cation exchange groups on the resin to the molar number of calcium ions was 2:1.5), and then the resin was washed with deionized water at a flow rate of 100mL / h for 4 hours. The resin was taken out, filtered, and vacuum dried to obtain 10.1g of calcium ion-loaded resin. The above operation was completed under nitrogen protection.

[0048] Determination of calcium ion loading: Accurately weigh about 0.1g of calcium ion-loaded resin and place it in a 100mL conical flask, add 10mL of 2% nitric acid, cover with a stopper, shake at room temperature for 6 hours, transfer all the resin and nitric acid to a 100mL volumetric flask, rinse the conical flask three times with deionized water and transfer it to a volumetric flask, dilute to the scale, and use ICP to determine the calcium ion concentration of the solution in the volumetric flask. After measurement and calculation, the calcium ion loading of the calcium ion-loaded resin is 2.52mmol / g.

[0049] (2) Loading hydroxyapatite crystals:

[0050] Add 10g of the above-mentioned ion-loaded resin and 60mL of deionized water to a 250mL three-necked flask and stir. Separately, dissolve 2.48g of trisodium phosphate and 0.202g of sodium hydroxide in 40mL of deionized water to form a mixed solution of phosphate and alkali, and add this solution dropwise to the above-mentioned three-necked flask (the ratio of the molar number of calcium ions loaded on the resin to the molar number of phosphate and alkali in the added mixed solution of phosphate and alkali is 1:0.6:0.2). Continue stirring for 12 hours after the addition is complete. After the reaction is completed, add 30mL of 20% sodium hydroxide solution to the three-necked flask under stirring. After the addition is complete, heat to 100°C and keep warm for 1 hour. Cool and filter, and wash the resin with deionized water until the washing solution is neutral. Filter, vacuum dry the resin, and obtain 12.6g of hydroxyapatite-loaded resin. Resin number: KRSr-03. The above operation was completed under nitrogen protection. Through X-ray diffraction (XRD) experiment ( Figure 3 ) proves the presence of hydroxyapatite in the resin. The XRD pattern of KRSr-03 sample is as follows Figure 2 shown.

[0051] Determine the loading amount of calcium ions and phosphorus ions: accurately weigh about 0.1g of the resin loaded with hydroxyapatite and place it in a 100mL conical flask, add 10mL of 2% nitric acid, cover the stopper, shake at room temperature for 6 hours, transfer all the resin and nitric acid to a 100mL volumetric flask, rinse the conical flask three times with deionized water and transfer it to the volumetric flask, dilute to the scale, and use ICP to determine the concentration of calcium and phosphorus in the solution in the volumetric flask. After measurement and calculation, the calcium and phosphorus loading amounts of the calcium ion loaded resin are 2.02 and 1.35mmol / g, respectively. The calcium ion loading amount is reduced relative to step (1) because the calcium ions are partially exchanged by ions in step (2).

[0052] Embodiment 4:

[0053] A strontium ion adsorbent is prepared by the following preparation method, which comprises the following steps:

[0054] (1) Loading calcium ions:

[0055] First, prepare the weakly acidic hydrogen-type cation exchange resin: transform 20g of the gel-type strong acidic cation exchange resin (wet, sodium type, water content 48.9%, exchange capacity 4.55mmol / g) of model 001×7 into the hydrogen type by conventional transformation method. Then suspend 1.89g of calcium hydroxide in 500mL of deionized water to form a calcium hydroxide suspension, add the above-transformed resin (the ratio of the molar number of cation exchange groups on the weakly acidic hydrogen-type cation exchange resin to the molar number of calcium ions is 2:1.1), and stir at room temperature for 24 hours. Filter, wash the resin with deionized water for many times, filter, and vacuum dry the obtained resin to obtain 9.94g of calcium ion-loaded resin.

[0056] Determination of calcium ion loading: Accurately weigh about 0.1g of calcium ion loaded resin and place it in a 100mL conical flask, add 10mL of 2% nitric acid, cover the stopper, shake at room temperature for 6 hours, transfer all the resin and nitric acid to a 100mL volumetric flask, rinse the conical flask three times with deionized water and transfer it to the volumetric flask, dilute to the scale, and use ICP to determine the calcium ion concentration of the solution in the volumetric flask. After measurement and calculation, the calcium ion loading of the calcium ion loaded resin is 2.61mmol / g.

[0057] (2) Loading hydroxyapatite crystals:

[0058] Add 10g of the above-mentioned ion-loaded resin and 60mL of deionized water to a 250mL three-necked flask and stir. Dissolve 2.57g of trisodium phosphate and 0.209g of sodium hydroxide in 40mL of deionized water, and add this solution dropwise to the above three-necked flask (the ratio of the molar number of calcium ions loaded on the resin to the molar number of phosphate and alkali in the mixed solution of added phosphate and alkali is 1:0.6:0.2). Continue stirring for 12 hours after the addition is complete. After the reaction is completed, add 30mL of 20% sodium hydroxide solution to the three-necked flask under stirring, and heat to 100℃ and keep warm for 1 hour after the addition is complete. Cool and filter, and wash the resin with deionized water until the washing solution is neutral. Filter, vacuum dry the resin, and obtain 12.1g of hydroxyapatite-loaded resin. Resin number: KRSr-04. The above operations are completed under nitrogen protection.

[0059] Determine the loading amount of calcium ions and phosphorus ions: accurately weigh about 0.1g of the resin loaded with hydroxyapatite and place it in a 100mL conical flask, add 10mL of 2% nitric acid, cover the stopper, shake at room temperature for 6 hours, transfer all the resin and nitric acid to a 100mL volumetric flask, rinse the conical flask three times with deionized water and transfer it to the volumetric flask, dilute to the scale, and use ICP to determine the concentration of calcium and phosphorus in the solution in the volumetric flask. After measurement and calculation, the calcium and phosphorus loading amounts of the calcium ion loaded resin are 2.14 and 1.30mmol / g, respectively. The calcium ion loading amount is reduced relative to step (1) because the calcium ions are partially exchanged by ions in step (2).

[0060] Verification example:

[0061] Verify the removal rate of strontium ions:

[0062] (1) No coexisting cations: About 0.1 g of hydroxyapatite-loaded resin was suspended in 25 mL of strontium chloride solution with a strontium ion concentration of 20 mg / L. The solution was shaken at room temperature for 12 h. The cesium ion concentration of the supernatant was determined by ICP. The strontium ion removal rate was calculated and shown in Table 1.

[0063] (2) With coexisting cations: About 0.1 g of hydroxyapatite-loaded resin was suspended in 25 mL of a solution consisting of strontium chloride, sodium chloride, calcium chloride, and magnesium chloride, wherein the concentrations of strontium ions, sodium ions, calcium ions, and magnesium ions were 20, 2000, 200, and 200 mg / L, respectively. The solution was shaken at room temperature for 12 h, and the cesium ion concentration of the supernatant was determined by ICP. The removal rate of strontium ions was calculated and shown in Table 1:

[0064] Table 1. Removal rate of strontium ions by adsorption of loaded hydroxyapatite resin

[0065]

[0066] As can be seen from Table 1, the adsorbent obtained by the present invention can achieve a strontium ion removal rate of 80.6-95.3% in the absence of coexisting cations, indicating that the resin has a high strontium ion removal rate; in the presence of coexisting cations, the strontium ion removal rate can reach 71.5-81.7%, indicating that the resin has a strong selectivity for strontium ions.

[0067] The above examples are only for illustrating the technical concept and technical features of the present invention, and cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a strontium ion adsorbent, wherein calcium ions are loaded onto a cation exchange resin by ion exchange, and then hydroxyapatite crystals are loaded into the resin, characterized in that: The following steps are involved: (1) Loading calcium ions: The cation exchange resin is reacted with the calcium hydroxide suspension / water-soluble calcium salt aqueous solution, so that the calcium ions are loaded on the cation exchange resin by ion exchange, and the cation exchange resin loaded with calcium ions is obtained for standby use; (2) Loading hydroxyapatite crystals: The calcium ion-loaded cation exchange resin obtained in step (1) is suspended in deionized water, and then a mixed solution of phosphate and alkali is added to the system to form hydroxyapatite precipitation inside the resin and load the hydroxyapatite crystals inside the cation exchange resin to obtain a spherical bead-like strontium ion adsorbent.

2. The preparation method according to claim 1, characterized in that: In step (1), the cation exchange resin is a strongly acidic cation exchange resin or a weakly acidic cation exchange resin, specifically a weakly acidic hydrogen-type cation exchange resin or a strongly acidic sodium-type cation exchange resin.

3. The preparation method according to claim 2, characterized in that: When the cation exchange resin is a weakly acidic hydrogen-type cation exchange resin, the specific method for loading calcium ions is as follows: suspending calcium hydroxide in deionized water to form a calcium hydroxide suspension, adding the weakly acidic hydrogen-type cation exchange resin, and stirring at room temperature for 0.1 to 24 hours to load the calcium ions on the weakly acidic hydrogen-type cation exchange resin through ion exchange.

4. The preparation method according to claim 3, characterized in that: The ratio of calcium hydroxide to water in the calcium hydroxide suspension is 0.1-100:0.1-1000, and the ratio of the molar number of cation exchange groups on the weakly acidic hydrogen type cation exchange resin to the molar number of calcium ions is 2:1-2:1.

5.

5. The preparation method according to claim 2, characterized in that: When the cation exchange resin is a strongly acidic sodium type cation exchange resin, the specific method for loading calcium ions is as follows: the strongly acidic sodium type cation exchange resin is loaded into a glass column, a water-soluble calcium salt aqueous solution is passed through the glass column at a flow rate of 0.1-1000 mL / h, and then the resin is washed with deionized water at a flow rate of 0.1-1000 mL / h for 0.1-24 h, so that the calcium ions are loaded on the cation exchange resin through ion exchange.

6. The preparation method according to claim 5, characterized in that: The water-soluble calcium salt aqueous solution is calcium chloride or calcium nitrate aqueous solution, the molar concentration of the solute in the water-soluble calcium salt aqueous solution is 0.001-10 mol / L, and the ratio of the molar number of cation exchange groups on the strongly acidic sodium type cation exchange resin to the molar number of calcium ions is 2:1-2:1.

5.

7. The preparation method according to claim 1, characterized in that: In step (2), the phosphate is any water-soluble phosphate, and the alkali is any strong alkali or weak alkali; in the mixed solution of the phosphate and the alkali, the concentration of the phosphate is 0.1-77%, and the concentration of the alkali is 0.1-50%; the ratio of the molar number of calcium ions loaded on the cation exchange resin loaded with calcium ions to the molar number of phosphate and alkali in the mixed solution of the phosphate and the alkali is (0.1-10):(0.1-10):(0.1-10).

8. The preparation method according to claim 1, characterized in that: In step (2), a mixed solution of phosphate and alkali is added to the system and the mixture is stirred at room temperature for reaction for 0.1-24 hours. After the reaction is completed, a sodium hydroxide solution is added dropwise under stirring conditions to make the concentration of sodium hydroxide in the system 4-6%. The temperature of the system is increased from room temperature to 80-100° C. and kept warm for 0.1-24 hours.

9. A strontium ion adsorbent prepared by the preparation method according to any one of claims 1 to 8, wherein the ion adsorbent is a spherical bead adsorbent.

10. Use of the strontium ion adsorbent according to claim 9 for adsorbing strontium ions.